Analysis Of Implementation Of Psak 112 Concerning Wakaf Accounting At Nazhir Center For Productive Waqf Development Mui, North Sumatra - Damayanti, Alfina; Sugianto; Atika (Universitas Dehasen Bengkulu, 2023)
This research is a qualitative research that aims to answer questions about how PSAK 112 is implemented at the MUI North Sumatra Productive Waqf Development Center and what are the obstacles faced by PSAK 112 at the MUI North Sumatra Productive Waqf Development Center Nazhir. The method used is descriptive qualitative research method. Data collection is done by interview, observation, and documentation. The data collection involved supervisors and treasurer of the North Sumatra MUI Productive Waqf Development Center. The results of the research obtained are that Nazhir Center for Productive Waqf Development MUI North Sumatra has implemented financial reports in accordance with PSAK 112 on recognition, measurement, presentation which includes a statement of financial position, a report on detailed assets, and a statement of cash flows. However, the notes to the financial statements are not fully in accordance with PSAK 112 because there is no written explanation regarding the nadir accounting policies applied by the Productive Waqf Development Center as well as information regarding nadir which is explained narratively in the financial statements. The MUI North Sumatra Productive Waqf Development Center is a social institution that relies on trust in the community. That way, it is expected that the nadir can include information about the nadir which is explained in a narrative manner by completing financial reports in accordance with PSAK 112.